Tackling Online Gambling through Criminal Law: Law Enforcement Strategies Against Cybercrime in Indonesia - Haribowo, Joko; Sudirman, Apri Setyawan; Kartiyoso, Andita Gunawan; Mursito (LifeSciFi, 2025)
This article discusses the handling of online gambling as a cybercrime in Indonesia, focusing on the legal framework, law enforcement challenges, and strategies for increasing effectiveness. The research methodology uses a normative-juridical approach with descriptive analysis, combining legislative and conceptual approaches to evaluate the Criminal Code (KUHP), the Electronic Information and Transactions (ITE Law), and related regulations. The results show that Articles 303 and 303 bis of the Criminal Code and Article 27 paragraph (2) of the Electronic Information and Transactions (ITE) Law provide the legal basis for prosecuting perpetrators through criminal sanctions, website blocking, and asset confiscation. However, law enforcement faces multidimensional obstacles, including technical (perpetrator anonymity, foreign servers, encryption, VPNs), structural (suboptimal inter-agency coordination), legal (regulatory gaps), and social (low public legal awareness and online promotion). An effective law enforcement strategy requires a holistic approach, including increasing the technological capacity of authorities, international cooperation, regulatory harmonization, the establishment of cross-agency task forces, proactive digital monitoring, public education, and the application of restorative justice principles through the use of confiscated assets for rehabilitation and education programs. This strategic integration is expected to suppress online gambling practices, mitigate socio-economic impacts, and strengthen the rule of law in the digital age.